P-276 Embryo development of fresh versus vitrified metaphase II oocytes in low prognosis patients: a retrospective sibling-oocyte monocentric study. (30th June 2022) - Boumerdassi, Y; Sadoun, M; Bouyer, J; Bennani Smires, B; Sarandi, S; Vinolas, C; Cedrin-Durnerin, I; Labrosse, J; Eustache, F; Peigné, M; Grynberg, M; Sifer, C
Abstract: Study question: Do fresh and vitrified/warmed oocytes have the same developmental potential in low prognosis patients defined by POSEIDON criteria? Summary answer: Embryos derived from vitrified/warmed oocytes show lower competence for embryo development when compared to those obtained from fresh oocytes in low prognosis patients. What is known already: The strategy of oocyte accumulation has been proposed for the management of low-prognosis patients with the aim to increase the number of oocytes available for fertilization and further the number of embryos. The effect of oocyte vitrification/warming on the embryo developmental potential has mainly been studied in oocyte donation programs. Investigations on sibling-oocyte failed to show difference in the morphological embryo development, but the evaluation stopped after 2-3 days of embryo culture. In addition, morphokinetic evaluation revealed delayed development of embryos derived from vitrified oocytes, from the first cleavage to the time of blastulation. Study design, size, duration: Single-center sibling-oocyte retrospective monocentric study including low-prognosis patients, defined by POSEIDON criteria, who had undergone an accumulation of oocyte strategy for managing their infertility, between November 2013 and January 2021. Only patients presenting fresh and vitrified/warmed oocytes at the time of insemination were analyzed for the sibling-oocyte comparison. Main study outcomes were fertilization, cleavage, blastulation rates, day-2 and day-5 embryo quality, and the rate of embryos available for transfer/cryopreservation. Participants/materials, setting, methods: Forty-five patients were included, with a mean age of 34.8 ± 3.4 years. Oocyte vitrification/warming was performed using the Cryotop method. Top-quality and good-quality embryos were defined at day-2 respectively as 4 and 3-5 adequate-sized blastomeres, without multinucleation and containing <20% of cytoplasmic fragmentation, and at day-5 according to Gardner and Schoolcraft's classification, top ≥B4 (AB/BA/AA) and good ≥ B3BB. Statistical analyses used mixed effects logistic regression to take into account the sibling-oocyte design. Main results and the role of chance: A total of 656 oocytes were inseminated, 225 fresh and 431 vitrified/warmed oocytes. The oocyte survival rate after warming was 82%, 95%CI [76-87%]. There was no difference between fresh and vitrified/warmed oocytes groups regarding the degeneration rate following ICSI (5.0% vs 4.8% respectively, p = 0.95), the fertilization rate (74.6% vs 71.4% respectively, p = 0.42) or the cleavage rate on day-2 (98.3% vs 95.4% respectively, p = 0.15). However, the embryo development was significantly different from day 2, with higher day 2 top-quality and good-quality embryos rates in the fresh oocytes group when compared to the vitrified/warmed oocytes group (top-quality: 38.3% vs 24.8% respectively, p = 0.01; good-quality 58.0% vs 45.2% respectively, p = 0.02). The same results were observed on blastocysts when extended culture was decided, with a higher blastulation rate in the fresh oocyte group (56.7% vs 31.7% respectively, p < 0.001) and higher top-quality and good-quality day 5 blastocyst rate (top-quality: 23.4% vs 5.6% respectively, p = 0.01; good-quality 23.9% vs 7.9%, p = 0.01).The rate of embryos available for transfer/cryostorage was similar in both groups (40, 7 % vs 38, 8 %, p = 0, 71). The cumulative live-birth rate was 33, 3% (4/45 from vitrified oocytes group, 5/45 from fresh oocytes group, 6/45 from mixed oocytes group). Limitations, reasons for caution: The retrospective nature of the study, on a limited number of limited number of patients represents an inherent limitation. Embryo assessment was subjective, the evaluator knowing the oocyte's source group. The impact of the morphological alterations observed in embryos derived from vitrified/warmed oocytes need to be confirmed with clinical outcomes. Wider implications of the findings: The majority of studies comparing fresh and vitrified/warmed oocytes were performed in egg-donation programs. This study focuses on low-prognosis patients, who reflect perhaps more the patients who consult in ART centers. Further prospective studies are needed to confirm our findings. Trial registration number: Not applicable